Language Policy and its Role in Shaping National Identity: A Macro-Linguistic Perspective - Muhammad Ali Imran; Nurasia Natsir (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to explore the relationship between language policy and national identity formation through a macro-linguistic lens. By employing qualitative case study methodology, the study analyzes the language policies of Canada, Belgium, and India, examining their impacts on social cohesion, cultural identity, and political stability. The research investigates specific language policies, such as bilingualism in Canada, collaborative language programs in Belgium, and multilingual education in India, assessing their effects on various communities within these nations. The findings indicate that inclusive language policies significantly enhance social cohesion and foster national pride, while exclusive policies can lead to division and marginalization. In Canada, continued support for bilingual education strengthens ties between linguistic groups. In Belgium, fostering mutual respect among linguistic communities mitigates political tensions. In India, promoting multilingual education protecs regional languages and cultivates a sense of unity. By focusing on the interplay between language and identity, this study highlights the critical importance of inclusive language policies in fostering social harmony and national unity. Ultimately, the findings provide actionable insights for policymakers, emphasizing the need for frameworks that recognize linguistic diversity while promoting dialogue and integration among different language communities. This research contributes to the understanding of effective strategies for strengthening national identity in an increasingly globalized world, reinforcing the idea that language can serve as a bridge rather than a barrier.